The Emergence of Conventions in Online Social Networks - Kooti, Farshad; Yang, Haeryun; Cha, Meeyoung; Gummadi, Krishna; Mason, Winter (Proceedings of the International AAAI Conference on Web and Social Media, 2021)
The way in which social conventions emerge in communities has been of interest to social scientists for decades. Here we report on the emergence of a particular social convention on Twitter—the way to indicate a tweet is being reposted and to attribute the content to its source. Initially, different variations were invented and spread through the Twitter network. The inventors and early adopters were well-connected, active, core members of the Twitter community. The diffusion networks of these conventions were dense and highly clustered, so no single user was critical to the adoption of the conventions. Despite being invented at different times and having different adoption rates, only two variations came to be widely adopted. In this paper we describe this process in detail, highlighting insights and raising questions about how social conventions emerge.